Upaya Pengurangan Risiko Bencana (MITIGASI) Letusan Gunung kelud oleh Masyarakat di Wilayah Kawasan Rawan Bencana (KRB) III Kabupaten Blitar - Sri Winarni; Agus Khoirul Anam; Rizal An Akhiruna (STIKes Patria Husada Blitar, 2016)
Indonesia is a country that has great case of natural disasters. One of disasters that recently occurred are the volcanic eruptions. Based on the interview with volunteer of kelud anchor in December 2015, there were communities that were less understand about disaster risk reduction efforts of the volcano. The purpose of the research was the efforts of disaster risk reduction (Mitigation) eruption of Kelud Mountain by the society in the area of Disaster-prone Areas (KRB) III Blitar Regency. This research used descriptive research design. The population of the research was all members of the community who live in area III KRB Kelud in Modangan. The sample was 60 people taken by quota sampling. The data collection was done by providing a closed-ended questionnaire multiple choice questions. Time data retrieval performed on 15-20 March 2016. The results showed that the public had the ability to either IE of 50% (30 people), enogh ability as 15% (10 people) and had less abilities i.e. as 35% (20 people). It was affected by the dissemination of prevention and disaster risk reduction. Recomendation for stakeholder of Modangan and Karangrejo village was to do socialitation in every or when there was sign of Kelud mountain activity.